REPRODUCTION PERFORMANCE OF CATTLE LIVESTOCK IN THE NATIONAL MEAT PRIVATE FRAME IN MUNA DISTRICT - Pagala, Muh. Amrullah; Nafiu, La Ode; Munadi, La Ode; Hidayat, Hidayat (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
Â Muna Regency is an area that has the largest beef cattle population in Southeast Sulawesi Province. The purpose of this study was to determine the performance of beef cattle reproduction carried out for 5 months in the Muna Regency. The method used in this research is purposive sampling method, while the data used are primary and secondary data. Primary data were obtained through interviews of 250 respondents while secondary data were obtained from the District, village and related government offices. The results showed that the reproductive performance of beef cattle in the Muna District showed a positive trend because it was supported by the population of beef cattle, ownership scale, availability of breeds, system and maintenance patterns, reproductive performance, lust cycle, and mating system.Â